POSITIVE RADIANCE The Aura Becomes You! - Shewchuk, Muriel (Operating Room Nurses Association of Canada Journal, 2005)
One’s attitude can change your life and your workplace! No matter how many “crankies”, or “BMWs” (not the expensive car, the “Bitch, Moan and Whiners”), you have to work with, YOU can break the cycle. You may feel it is not your job to fix the world. But it is your responsibility to make things good for yourself, and this includes your work environment. By making things right, through the use of your own positive attitude, you cannot help but share those positive vibes with those around you. Imagine a positive aura surrounding you. Mind over matter is very powerful! So what are the keys to this positive radiance?